Comparison of East‐Asia and West‐Europe cohorts explains disparities in survival outcomes and highlights predictive biomarkers of early gastric cancer aggressiveness. Issue 5 (9th December 2021) - Pereira, Carla; Park, Ji‐Hyeon; Campelos, Sofia; Gullo, Irene; Lemos, Carolina; Solorzano, Leslie; Martins, Diana; Gonçalves, Gilza; Leitão, Dina; Lee, Hyuk‐Joon; Kong, Seong‐Ho; André, Ana; et al.
Abstract: Surgical resection with lymphadenectomy and perioperative chemotherapy is the universal mainstay for curative treatment of gastric cancer (GC) patients with locoregional disease. However, GC survival remains asymmetric in West‐ and East‐world regions. We hypothesize that this asymmetry derives from differential clinical management. Therefore, we collected chemo‐naïve GC patients from Portugal and South Korea to explore specific immunophenotypic profiles related to disease aggressiveness and clinicopathological factors potentially explaining associated overall survival (OS) differences. Clinicopathological and survival data were collected from chemo‐naïve surgical cohorts from Portugal (West‐Europe cohort [WE‐C]; n = 170) and South Korea (East‐Asia cohort [EA‐C]; n = 367) and correlated with immunohistochemical expression profiles of E‐cadherin and CD44v6 obtained from consecutive tissue microarrays sections. Survival analysis revealed a subset of 12.4% of WE‐C patients, whose tumors concomitantly express E‐cadherin_abnormal and CD44v6_very high, displaying extremely poor OS, even at TNM stages I and II. These WE‐C stage‐I and ‐II patients tumors were particularly aggressive compared to all others, invading deeper into the gastric wall ( P  = .032) and more often permeating the vasculature ( P  = .018) and nerves ( P  = .009). A similar immunophenotypic profile was found in 11.9% of EA‐C patients, but unrelated to survival. Tumours, from stage‐I and ‐II EA‐C patients, that display both biomarkers, also permeated more lymphatic vessels ( P  = .003), promoting lymph node (LN) metastasis ( P  = .019), being diagnosed on average 8 years earlier and submitted to more extensive LN dissection than WE‐C. Concomitant E‐cadherin_abnormal/CD44v6_very‐high expression predicts aggressiveness and poor survival of stage‐I and ‐II GC submitted to conservative lymphadenectomy. Abstract : What's new? Surgical resection with lymphadenectomy and perioperative chemotherapy is the mainstay of treatment for loco‐regional gastric cancer. However, while South Korea has the highest gastric cancer incidence rate worldwide, the mortality rate is low compared to Western countries like Portugal. This study shows that the survival disparities between the two regions may be explained by earlier cancer detection and increased removal of lymph nodes. The findings support the assessment of concomitant E‐cadherin and CD44v6 expression in tumour biopsies from stage I and II gastric cancer patients and larger removal of lymph nodes in those patients presenting a high dissemination probability.